Impact of branching angle on neointimal coverage of drug-eluting stents implanted in bifurcation lesions. Issue 8 (December 2016) - Watanabe, Makoto; Uemura, Shiro; Kita, Yoko; Sugawara, Yu; Goryo, Yutaka; Ueda, Tomoya; Soeda, Tsunenari; Okayama, Satoshi; Okura, Hiroyuki; Kume, Teruyoshi; Saito, Yoshihiko
Abstract : Objectives: To investigate the impact of branching angle (BA) on neointimal coverage of drug-eluting stents (DESs) in bifurcation lesions. Background: Previous experimental studies indicated that BA influences the local flow turbulence and wall shear stress, which are associated with neointimal coverage of DESs. Methods: Fifty-five bifurcation lesions in 47 patients were evaluated by serial optical coherence tomography (OCT) before DES implantation and at follow-up. Neointimal coverage was assessed in cross-sectional OCT images containing the side branch; regions including the side branch ostium (SO) and vessel wall (VW) were assessed separately. BA was measured using angiography (Angio-BA) and longitudinal OCT imaging (OCT-BA). Results: In the SO region, a significant negative correlation was found between the uncovered strut percentage and Angio-BA or OCT-BA ( r =−0.41, P =0.0024; r =−0.33, P =0.0167, respectively) and a significant positive correlation was found between Angio-BA and average neointimal thickness ( r =0.31, P =0.025), whereas no correlation was observed between OCT-BA and average neointimal thickness ( r =0.20, P =0.158). In the VW region, no correlation was found between Angio-BA or OCT-BA and the uncovered strut percentage or average neointimal thickness. Conclusion: BA influence the neointimal coverage over DES struts in the SO at coronary bifurcation lesions, but not in those attached to the VW.